Invisible Assets, Visible Problems: An Analysis of Issues in the Management of Intangible Assets in the Indonesian Government - Nur Aini; Jamaluddin Jamaluddin; Iskandar Iskandar (West Science Interdisciplinary Studies, 2026)
Government agencies' ownership of intangible assets increases each year in line with the expansion of digitization programs; however, this is not always accompanied by optimal management. Many intangible assets eventually fall into disuse—either because they are no longer relevant to the agency's needs or have been replaced by new systems—yet they remain recorded as assets in government financial statements. This issue has ultimately drawn the attention of the Supreme Audit Agency of the Republic of Indonesia (BPK RI). During the 2014–2023 period, the BPK RI identified intangible assets that were no longer in use but were still recorded as current assets in the financial reports of ministries and agencies. Using content analysis, this article aims to describe issues in the management of intangible assets within the Indonesian government, with a focus on those no longer in use. The analysis results show that the BPK RI recommended that ministries and agencies write off these intangible assets because they are considered non-compliant with existing regulations, which stipulate that only intangible assets that are still in use may be recorded.